2014
DOI: 10.1083/jcb.201306085
|View full text |Cite
|
Sign up to set email alerts
|

Motor-driven marginal band coiling promotes cell shape change during platelet activation

Abstract: During platelet activation, motor protein-induced coiling of the microtubule-based marginal band leads to the cells’ characteristic spherical shape, whereas actomyosin-mediated compression of the coil results in new microtubule polymerization in a smaller ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
146
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(151 citation statements)
references
References 29 publications
5
146
0
Order By: Relevance
“…Microtubule coils in platelets at early stages of spreading were disrupted and spread platelet microtubule networks failed to form. Furthermore, the dynamics of microtubules were affected with observed microtubule coils failing to undergo the characteristic twisting of control platelets (as observed by Diagouraga et al) and appearing to depolymerize more rapidly than in controls. Thus, it would appear that there is an effect of SMIFH2 on microtubules in addition to the inhibition of actin polymerization.…”
Section: Discussionmentioning
confidence: 79%
“…Microtubule coils in platelets at early stages of spreading were disrupted and spread platelet microtubule networks failed to form. Furthermore, the dynamics of microtubules were affected with observed microtubule coils failing to undergo the characteristic twisting of control platelets (as observed by Diagouraga et al) and appearing to depolymerize more rapidly than in controls. Thus, it would appear that there is an effect of SMIFH2 on microtubules in addition to the inhibition of actin polymerization.…”
Section: Discussionmentioning
confidence: 79%
“…The blood was collected in a BD Vacutainer tubes with 3.2% sodium citrate (Fisher Scientific). Prior to centrifugation, the whole blood collected was gently agitated at room temperature for 1 h to restore platelets partially activated during the withdrawal of blood back to the resting state . An anticoagulant, acid citrate dextrose (ACD), was then added to the blood at a ratio of 1:7 (ACD:blood).…”
Section: Methodsmentioning
confidence: 99%
“…It was recently 26 shown that dynein slides microtubules apart to reorganize the marginal microtubule band of the resting platelet after activation. These forces extend the marginal band and induce coiling and are followed by actomyosin-mediated compression forces.…”
Section: Discussionmentioning
confidence: 99%